1973
DOI: 10.1136/bmj.1.5849.311
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Sympathomimetic Amines and Antidepressant Agents in Man

Abstract: SummaryIntravenous infusions of phenylephrine, noradrenaiine, adrenaline, and isoprenaline were given to healthy human volunteers after five to seven days on phenelzine, tranylcypromine, or imipramine, and cardiovascular responses were compared with those observed under control conditions. With monoamine oxidase inhibitors there was a 2-2k fold potentiation of the pressor effect of phenylephrine, but no clinically significant potentiation of cardiovascular effects of noradrenaline, adrenaline, or isoprenaline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
8

Year Published

1975
1975
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(37 citation statements)
references
References 18 publications
1
28
0
8
Order By: Relevance
“…80,84 Patients on MAOI/RIMA do not have clinically significant potentiation of cardiovascular effects of iv infusions of norepinephrine or epinephrine. 82,88 Vasopressors at concentrations contained in local anesthetics are not likely to be significantly potentiated in otherwise healthy patients on MAOI. 88 Direct-acting sympathomimetics may be used safely (grade C).…”
Section: Are Maoi Associated With Atypical Responses To All Catecholamentioning
confidence: 99%
See 1 more Smart Citation
“…80,84 Patients on MAOI/RIMA do not have clinically significant potentiation of cardiovascular effects of iv infusions of norepinephrine or epinephrine. 82,88 Vasopressors at concentrations contained in local anesthetics are not likely to be significantly potentiated in otherwise healthy patients on MAOI. 88 Direct-acting sympathomimetics may be used safely (grade C).…”
Section: Are Maoi Associated With Atypical Responses To All Catecholamentioning
confidence: 99%
“…82,88 Vasopressors at concentrations contained in local anesthetics are not likely to be significantly potentiated in otherwise healthy patients on MAOI. 88 Direct-acting sympathomimetics may be used safely (grade C).…”
Section: Are Maoi Associated With Atypical Responses To All Catecholamentioning
confidence: 99%
“…Tricyclic antidepressive drugs such as imipramine and proptriptyline produce 2-9 fold potentiation (Boakes et al, 1973;Svedmyr, 1968). Increased NA sensitivity during amitriptyline therapy has also been demonstrated by using the present method .…”
Section: Studies On the Interaction Between Mianserin And Noradrenalimentioning
confidence: 71%
“…In a related study, Boakes et al [ 19] reported the development of atrial ectopic beats in 1 of 5 healthy volunteers who had received 75 mg/day for 5 days upon the in travenous infusion of adrenaline.…”
Section: Discussionmentioning
confidence: 99%